T‑Cells from HLA-B57:01+ Human Subjects Are Activated with Abacavir through Two Independent Pathways and Induce Cell Death by Multiple Mechanisms - Bell, Catherine C; Faulkner, Lee; Martinsson, Klara; Farrell, John; Alfirevic, Ana; Tugwood, Jonathan; Pirmohamed, Munir; Naisbitt, Dean J; Park, B. Kevin (Chemical research in toxicology, 2013)
Susceptibility to abacavir hypersensitivity has been attributed to possession of the specific human leukocyte antigen allele HLA-B*57:01. HLA-B*57:01-restricted activation of CD8+ T-cells provides a link between the genetic association and the iatrogenic disease. The objectives of this study were to characterize the functionality of drug-responsive CD8+ T-cell clones generated from HLA-B*57:01+ drug-naive subjects and to explore the relationship between abacavir accumulation in antigen presenting cells and the T-cell response. Seventy-four CD8+ clones expressing different Vβ receptors were shown to proliferate and kill target cells via different mechanisms when exposed to abacavir. Certain clones were activated with abacavir in the absence of antigen presenting cells. Analysis of the remaining clones revealed two pathways of drug-dependent T-cell activation. Overnight incubation of antigen presenting cells with abacavir, followed by repeated washing to remove soluble drug, activated approximately 50% of the clones, and the response was blocked by glutaraldehyde fixation. In contrast, a 1 h antigen presenting cell pulse did not activate any of the clones. Accumulation of abacavir in antigen presenting cells was rapid (less than 1 h), and the intracellular concentrations were maintained for 16 h. However, intracellular abacavir was not detectable by mass spectrometry after pulsing. These data suggest that T-cells can be activated by abacavir through a direct interaction with surface and intracellular major histocompatibility complex (MHC) molecules. With the former, abacavir seemingly participates in the MHC T-cell receptor binding interaction. In contrast, the latter pathway likely involves MHC binding peptides displayed as a consequence of abacavir exposure, but not abacavir itself.